Existence and Stability Results for Impulsive Stochastic Functional Integrodifferential Equation with Poisson Jumps - Anguraj, A.; Ravikumar, K. (Journal of Applied Nonlinear Dynamics, 2026)
In this article we present the existence, uniqueness and stability of mild solutions for impulsive stochastic functional integro diﬀerential equations with non-Lipschitz condition. The mild solution is obtained by using a resolvent operator in a diﬀerent sense and the results are proved by using the method of successive approximation and Bihari’s inequality.